Optimizing Social Engagement Through Community-Based English Education: a Case Study of Beraban English Club at Nuanu Social Fund - Ganang Aditiyo Prakoso; I Wayan Adi Pratama; Zevania Damayanti Iskandar (International Journal of Travel, Hospitality and Events, 2026)
This study explores the optimization of social engagement strategies through a community-based English education program Beraban English Club implemented by Nuanu Social Fund in Beraban Village, Tabanan, Bali. Utilizing a qualitative-descriptive research approach, data were collected through participatory observation, pre-test and final-test evaluation, in-depth interviews, and activity documentation involving 7 active youth participants from Karang Taruna GAPERA and key stakeholders from Nuanu Social Fund. Drawing on experiential learning theory (Kolb, 1984), the study examined how participatory and community-based learning approaches could enhance emotional involvement, peer collaboration, and contextual learning experiences. The results demonstrate that while social engagement levels remained moderate due to external factors related to local customs and responsibilities, the program achieved significant improvements in English proficiency (from 61% to 82%, representing a 34% increase) and strengthened community connections. The study identifies critical factors influencing engagement success, including participant recruitment methods, scheduling considerations relative to local cultural calendars, and the importance of personalized motivational strategies. These findings contribute to understanding how educational social events can effectively combine language skill development with sustainable community social impact. This research offers both theoretical implications for community learning models and practical recommendations for future initiatives by Nuanu Social Fund and similar social organizations seeking to enhance youth empowerment through culturally-sensitive, participatory education programs.